2020
DOI: 10.3389/fmicb.2020.00353
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum Depletion Property and Microbial Community Shift After Bioremediation Using Bacillus halotolerans T-04 and Bacillus cereus 1-1

Abstract: Bioremediation of crude oil contaminated environments is an economical, lowmaintenance, environmentally friendly technology and has attracted increasing attention in recent years. In the present study, two efficient crude oil degrading bacteria strains were isolated from soils contaminated with crude oil. Phylogenetic analysis suggested they belonged to genus Bacillus, and were designated as Bacillus cereus T-04 and Bacillus halotolerans 1-1. The crude oil depletion of each strain under different conditions wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 38 publications
0
11
0
1
Order By: Relevance
“…Likewise, Kuang et al (2018) showed that the percentage of Proteobacteria increased in oilcontaminated soil (Shengli oil field, China) compared to unpolluted soil. Nevertheless, Deng et al (2020) reported that after bioaugmentation of Bacillus sp. in crude oil-contaminated soil (Shannxi Province, Yanchang), the original microbial diversity was recovered at the phylum level.…”
Section: Diversity Of Microbial Groups In the Crude Oil-fortified Sandy Loam Soilmentioning
confidence: 99%
“…Likewise, Kuang et al (2018) showed that the percentage of Proteobacteria increased in oilcontaminated soil (Shengli oil field, China) compared to unpolluted soil. Nevertheless, Deng et al (2020) reported that after bioaugmentation of Bacillus sp. in crude oil-contaminated soil (Shannxi Province, Yanchang), the original microbial diversity was recovered at the phylum level.…”
Section: Diversity Of Microbial Groups In the Crude Oil-fortified Sandy Loam Soilmentioning
confidence: 99%
“…Por otro lado, la capacidad de producir esporas hace que las especies de Bacillus puedan ocupar varios hábitats ofreciendo características importantes en bio-remediación de aguas residuales industriales (35,36), en el cuidado de la calidad del agua en acuicultura (37), en una acuicultura sustentable (37) y de amplio uso como probióticos en diferentes modelos animales (37,38). En peces su aplicación tiene implicaciones directas en mejorar el crecimiento y la conversión alimenticia (38), la resistencia al estrés (38), la inmunoestimulación y resistencia a enfermedades (39) y de manera general en su bienestar (39).…”
Section: Discussionunclassified
“…Bacillus cereus Crude oil Degradation [17] Bacillus methylotrophicus Chromate, Glutathione [18] Burkholderia Fungorum PAHs Contaminated Soil [19] Mucor hiemalis Heavy metals [20] Mucor circinelloides Heavy metals [21] Penicillium citrinum, Penicillium pinophilum,…”
Section: Glyphosate Degradationmentioning
confidence: 99%